Simultaneous time-temperature-thickness superposition theoretical and statistical modelling of convective drying of guava - Kek, Siok Peng; Chin, Nyuk Ling; Yusof, Yus Aniza (Springer, 2014)
Modelling studies of guava drying and quality are presented using theoretical and statistical models by varying temperature from 55 to 75 °C and slice thickness from 3 to 9 mm. The quality of dried fruit was measured for its water activity, colour, vitamin C, and texture. The superposition technique with Midilli-Kucuk model showed efficiency in modelling the drying process with R 2  = 0.9991. The second-order polynomial equations adequately described the quality of dried guava with regression coefficient, R 2  > 0.7. Drying time was a good function of temperature and thickness (P < 0.001); water activity, colour and vitamin C showed strong dependence on temperature (P < 0.1); while texture was mainly influenced by its thickness (P < 0.005). The optimum drying temperature of 70 °C at slice thickness of 6 mm was determined using the desirability function method. Simultaneous modelling using the theoretical and statistical drying models provides information on water diffusion and evaporation with the drying responses and factors.